Rooting Governance and its Legal Nature - Kadhim, Rusul; Abdulqadir, Ban (Journal of Legal Sciences, 2024)
Tax governance is a set of legal means that directs the tax administration to deal in good faith with taxpayers based on transparency, integrity and accountability while ensuring the achievement of tax justice and works to introduce advanced means by which it deals with all stakeholders. In this study, we try to explain its rooting and legal nature by shedding light on the position of some international organizations and their internal legislation in the context of public finance.